Efeitos de lasers de alta potência na superfície de cerâmicas vítreas de dissilicato de lítio e sua resistência de união à dentina humana - Feitosa, Fernanda Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The aim of this study was to evaluate the efficiency of irradiation with high-power lasers and the influence of silane application before or after irradiation with lasers on the bond strength between lithium disilicate glass-ceramic, resin cement and human dentin. Fifty truncated-cones ceramic specimens (n=10) were randomly divided into 5 groups: Control- etching with hydrofluoric acid 10% for 1 min and application of silane; 2- Er - Er:YAG laser irradiation (200 mJ and 10 Hz), followed by etching with hydrofluoric acid 10% for 1 min and application of silane; 3- Sil + Er - etching with hydrofluoric acid 10% for 1 min, silane application and irradiation with Er: YAG laser in the same parameters as the previous group; 4- Nd:YAG laser - irradiation with Nd: YAG laser (120 mJ and 10 Hz), followed by etching with hydrofluoric acid 10% for 1 min and application of the silane, 5- Sil + Nd- Etching with hydrofluoric acid 10% for 1 min, silane application and irradiation with Nd: YAG laser on the same parameters as the previous group. After treatment, the ceramic specimens were cemented with dual cure resin cement to the dentin of 50 human molars included in acrylic resin. After storage for 24 h it was submitted to tensile test in a universal testing machine with 10 kgf load cell and constant speed of 1 mm/min. Data were submitted to ANOVA 2-way and Dunnet test (α = 5%). The analysis of fracture patterns were analyzed in stereomicroscope. In addition were made 15 ceramic specimens in cylindrical shape, subjected to the same treatment of the above groups (n = 3) and used for analysis of the contact angle analysis and scanning electron microscope. The Dunnet test showed significant differences between Control group (9.42 ± 2.27 MPa) and Er group (19.25 ± 3.7 MPa) and Sil + Er (14.11 ± 4.11 MPa). ANOVA 2-way (p <5%) for Laser Type (p <0.0001) and Technical of Silanization (p = 0.0002) showed significant differences for both factors, but not for their interaction. Thus, the irradiation with Er:YAG laser (16,68 MPa) was more effective than irradiation with Nd:YAG laser (8,19 MPa). The technique of silanization after laser irradiation was more effective (14,46 MPa) than the previous silanization (10,41 MPa). The analysis of fractures showed a prevalence of adhesive failures on dentin and ceramic for the Control group; Nd, Sil + Nd e Sil + Er had a prevalence of adhesive failures in ceramics, and Er group presented predominance of cohesive failures in cement. The analysis of contact angle was submitted to ANOVA 1-way and Tukey test, with significant differences between the groups (p <0.0001). Groups with silanization previous to laser irradiation (Sil + Er = 45,60b degrees; Sil + Nd = 52,10b degrees) had contact angles greater than the other groups. The Scanning Electron Microscopy images showed the presence of a silane layer on the ceramic surface in Sil + Nd group, and an apparent casting of the ceramic surface in Sil + Er group. For Er and Nd Groups was possible to see changes in the normal pattern of ceramic structure, interspersed with areas similar to conventional standard control group after etching with hydrofluoric acid. It is concluded that treatment with Er:YAG laser associated with etching with hydrofluoric acid at 10% for 1 min gives the highest bond strength results and the lower contact angle, resulting in a recommended treatment. Treatment with silane previously to laser irradiation improved bond strength only when associated with the Er:YAG laser, which probably occurred by the efficiency of Er: YAG laser irradiation, and not due to the silanization technique.

O objetivo desse estudo foi avaliar a eficiência da irradiação com lasers de alta potência e a influência da aplicação do silano previa ou posteriormente à irradiação com os lasers na resistência de união entre cerâmica vítrea de dissilicato de lítio, cimento resinoso e dentina humana. Foram confeccionados 50 espécimes tronco-cônicos de cerâmica (n=10), divididos aleatoriamente em 5 grupos: 1- Controle- Condicionamento com ácido hidrofluorídrico 10% por 1 min e aplicação do silano; 2- Er:YAG – irradiação com laser Er:YAG (200 mJ e 10 Hz), seguido do condicionamento com ácido hidrofluorídrico 10% por 1 min e aplicação do silano; 3- Silano + Er:YAG – Condicionamento com ácido hidrofluorídrico 10% por 1 min, aplicação do silano e irradiação com laser Er:YAG nos mesmo parâmetros do grupo anterior; 4- Nd:YAG – irradiação com laser Nd:YAG (120 mJ e 10 Hz), seguido de condicionamento com ácido hidrofluorídrico 10% por 1 min e aplicação do silano, 5- Silano + Nd:YAG - Condicionamento com ácido hidrofluorídrico 10% por 1 min, aplicação do silano e irradiação com laser Nd:YAG nos mesmo parâmetros do grupo anterior. Após os tratamentos os espécimes cerâmicos foram cimentados com cimento resinoso de presa dual à superfície de dentina de 50 molares humanos incluídos em resina acrílica ativada quimicamente. Após armazenamento por 24 h foi realizado o ensaio de tração em máquina de ensaios universais com célula de carga de 10 KgF e velocidade constante de 1mm/min. Os dados obtidos foram submetidos à ANOVA 2-fatores e teste de Dunnet (α=5%). A análise dos padrões de fratura foram analisadas em estereomicroscopio. Adicionalmente foram confeccionados 15 espécimes em cerâmica no formato cilíndrico, submetidos aos mesmo tratamentos dos grupos anteriores (n=3) e utilizados para análise do ângulo de contato e análise em microscópio eletrônico de varredura. O teste de Dunnet mostrou diferenças significativas entre o grupo controle (9,42 ± 2,27 MPa) e os grupos Er (19,25 ± 3,7 MPa) e Sil+Er (14,11 ± 4,11 MPa). A análise de variância (p<5%) para os fatores Tipo de Laser (p<0,0001) e Técnica de Silanização (p=0,0002) mostraram diferenças significativas para os dois fatores, porém não para sua interação. Assim, a irradiação com Er:YAG (16,68 MPa) mostrou-se mais eficiente que a irradiação com Nd:YAG (8,19 MPa). A técnica de silanização posterior à irradiação com laser (14,46 MPa) também se mostrou superior à silanização previa (10,41 MPa). Quanto à análise de fraturas, o grupo Controle teve prevalência de falhas adesivas em dentina e em cerâmica; os grupos Nd, Sil + Nd e Sil + Er tiveram prevalência de falhas adesivas em cerâmica, e o grupo Er apresentou predominância de falhas coesivas no cimento. A análise do ângulo de contato foi submetida aos testes ANOVA 1-fator e Tukey, apresentando diferenças significativas entre os grupos (p<0,0001). Os grupos com silanização prévia (Sil + Er = 45,60b graus; Sil + Nd = 52,10b graus) apresentaram ângulos de contato superiores aos demais, e semelhantes entre si. As imagens de Microscopia Eletrônica de Varredura mostram a presença da camada de silano sobre a superfície cerâmica no grupo Sil + Nd, e uma aparente fundição à superfície cerâmica no grupo Sil + Er. Para os Grupos Er e Nd foi possível verificar modificações no padrão normal da estrutura da cerâmica, entremeadas por áreas semelhantes ao padrão convencional do grupo Controle após condicionamento com ácido hidrofluorídrico. Conclui-se que o tratamento com laser de Érbio associado ao condicionamento com ácido hidrofluorídrico a 10% por 1 min apresenta os melhores resultados de resistência de união e ângulo de contato. O tratamento com silano previamente à irradiação melhorou a resistência de união em relação ao grupo Controle apenas quando associado ao laser de Érbio.
Effects of high power laser irradiation on lithium di-silicate glass ceramic surface and bond strength to human dentin
Keywords: Bond strength; Ceramic; Er:YAG Lasers; Nd:YAG Lasers; Silanes; Cerâmica; Lasers de Er-YAG; Lasers de Nd-YAG; Silanos